Digested sludge-degrading and hydrogen-producing bacterial floras and their potential for biohydrogen production. (May 2017) - Kuribayashi, Kyohei; Kobayashi, Yoshiki; Yokoyama, Kazuhira; Fujii, Katsuhiko
Abstract: Digested sludge (DS) is a recalcitrant waste produced by anaerobic digestion of excess sludge. Although biological wastes have received attention as a substrate for hydrogen fermentation, DS has not been well examined as a substrate for the fermentation. In this study, we found and characterized DS-degrading/hydrogen-producing bacterial floras. Soil and cattle faecal samples were enriched by DS supplementation, and repeated subculture of the samples produced three bacterial floras showing stable hydrogen production (0.95–1.62 ml H2 /g-dried DS). They comprised unique members with some belonging to novel genera ( Fonticella, Gracilibacteri and Romboutsia ). The culture supernatant exhibited xylanase, chitinase and keratinase activities, suggesting that bacterial members in the floras degrade xylan, chitin, and protein in DS to produce hydrogen. While there are many articles of hydrogen fermentation from excess sludge, our study is the first report on hydrogen fermentation from untreated DS as a fermentation substrate. Highlights: Digested sludge (DS) is a recalcitrant byproduct of anaerobic digestion. Bacterial floras producing hydrogen from DS as a carbon source were found. The bacterial floras were implied to produce several hydrolase to assimilate DS. The bacterial floras contained several strains belonging to novel genera. The study provides insights for understanding mechanisms of hydrogen production from DS.